CREATION MODEL OF TIME-DEPENDENT LOWERING OPERATOR AND RAISING OPERATOR UNDER TIME-DEPENDENT EXTERNAL DAMPING FORCE SIMPLE HARMONIC OSCILLATOR : - Moonsri, Piyarut; Yakaw, Prisana; Hutem, Artit (PSRU Journal of Science and Technology, 2020)
In this research paper, we developed a theory and model of the forced simple harmonic oscillators in quantum mechanics system in a framework of a general approach to the Heisenberg picture. We can be used the time-dependent Hamiltonian for the forced simple harmonic oscillators. We use first-order ordinary linear differential equation to solve the time-dependent lowering operator and raising operator. We evaluate the lowering operator and raising operator as the function of time for particle mass depend on the parameter frequency of oscillation , the damping coefficient of particle bound in the simple harmonic oscillator potential, the initial force .